Envisioning the future of behavioral decision-making: A systematic literature review of behavioral reasoning theory - Aditya Kumar Sahu; R.K. Padhy; Amandeep Dhir (Elsevier Australia, 2022)
Behavioral theories have been extensively referred to in consumer behavior literature to understand the factors influencing user intentions and behavior. Behavioral reasoning theory (BRT) is a relatively new theory that determines the linkage between beliefs, reasons, motives, intentions, and behavior. This study conducts a systematic literature review (SLR) to synthesize the existing body of knowledge around BRT. The present SLR critically examines the origin of this theory and its linkages with other behavioral theories, thus providing insightful knowledge on its foundations. Further, it presents the state-of-the-art research knowledge, research themes, implications, and future directions related to BRT literature. Our analysis shows that the reasons for and reasons against construct plays an important role in predicting consumer behavior. This study also finds that research related to BRT is growing rapidly and needs methodological advancements. These findings will enable scholars and practitioners to better understand how BRT works, what its strengths and potential are, the contexts in which it has been utilized, its existing limitations, and the sort of methodological advancements needed in future studies on marketing.